Rediscovery of Diospyros bambuseti (Ebenaceae) in Thailand: Emended taxonomic description, lectotypification, and phylogenetic placement - Duangjai, Sutee; Sinbumroong, Aroon; Chalermwong, Porntawat; Suekaew, Padungsak; Suddee, Somran (Phytotaxa, 2022)
Diospyros bambuseti is a rare species endemic to Thailand that was previously known only from type specimens. The only male specimens of this species were collected in 1930 from a bamboo forest in Aranya Prathet district, now Sa Kaeo Province, Thailand. Both male and female plants were rediscovered in Surat Thani Province, upper Peninsular Thailand during 2015–2020. In this work, we provide an emended description, detailed ecological data, photographs, and illustrations of recently collected specimens. We performed lectotypification and investigated the phylogenetic placement and sister taxa of D. bambuseti based on the DNA sequences of eight plastid regions. D. bambuseti is closely related to D. ehretioides, D. fasiculosa, and D. venosa. Finally, we provide a detailed morphological comparison of D. bambuseti with related species.